Split thickness buccal mucous membrane grafts and β irradiation in the treatment of recurrent pterygium. Issue 12 (1st December 1998) - Forbes, Jennifer; Collin, Richard; Dart, John
Abstract : BACKGROUND: Pterygium is a common problem and after surgical removal may recur in up to 80% of cases, depending on the technique of primary excision. Recurrent pterygia can be aggressive and repeated excision may result in severe conjunctival scarring and shortening, resulting in insufficient conjunctiva to perform further grafting and lid surgery. When there is insufficient autologous conjunctiva, mucous membrane must be obtained from other sites. Full thickness buccal mucous membrane grafts have been described, but they may result in a beefy red appearance, with graft contraction and a poor tear film. METHOD: The use of split thickness buccal mucous membrane grafts is described in three patients with recurrent pterygium, two in combination with lamellar keratoplasty. β Irradiation was used as adjuvant therapy in all cases. RESULTS: In all three cases an acceptable cosmetic appearance was achieved, with no recurrence of the pterygium, and a good range of eye movements. CONCLUSIONS: It is recommended that split thickness buccal mucosal grafts, combined with β irradiation, should be considered in complex cases of pterygium recurrence when there is insufficient autologous conjunctiva and conjunctival shortening with restricted eye movements.